Performance Analysis of a New Integrated Gasification Technology Driven by Biomass for Hydrogen and Electricity Cogeneration with a Dual Chemical Looping Process. Issue 10 (17th June 2016) - Zhu, Lin; Chen, Hu; Zhang, Zheng
Abstract: A process based on biomass gasification integrated with a dual chemical looping technology, namely, chemical looping air separation and iron‐based chemical looping combustion, is proposed to investigate the performance of hydrogen and electricity cogeneration from a thermodynamic perspective. The effects of four vital ratios, namely, steam to biomass, oxygen to biomass, Fe2 O3 to carbon, and flue gas to Mn2 O3, on the thermodynamic performances of this process are investigated. Meanwhile, a T – Q diagram is involved in the validation of the feasibility of heat‐exchange networks in this process. In parallel, the system efficiencies (such as total energy efficiency and exergy efficiency) are evaluated. The exergy destruction of this process is also analyzed. As a result, the total energy and exergy efficiencies are calculated to be 66.23 and 58.10 %, respectively. Most exergy destruction is caused by the gasifier, which accounts for 40.90 % of the total exergy destruction. Abstract : Power from waste : Biomass is converted into decarbonized energy vectors (hydrogen and electricity) through a process based on biomass gasification integrated with a dual chemical looping technology (BGDCL), namely, chemical looping air separation (CLAS) and iron‐based chemical looping combustion (Fe‐CLC).